Effect of Magnetic Field on Natural Convection flow in a Prism Shaped Cavity Filled with Nanofluid. (2017) - Parvin, Salma; Akter, Afroza
Abstract: The paper executes the laminar natural convection flow and heat transfer inside a prismatic enclosure with non-uniform temperature distribution maintained at the bottom wall. The side walls are insulated and the remaining walls are cooled at temperature T c . A magnetic field of strength B0 is applied horizontally normal to the side walls. The water- Al 2 O 3 nanofluid is used as the heat transfer medium through the enclosure. Finite Element Method of Galerkin's weighted residual scheme is used to solve the transport equations with appropriate boundary conditions. The effect of Hartman number Ha (0 to 50) for nanofluid as well as for the base fluid on isotherms, streamlines and heat lines, local and average heat transfer are presented graphically. The calculations have been performed for Prandtl number Pr = 6.2. Results indicate that the heat transfer rate is significantly affected by increasing the mentioned parameter.